Determinants for conducting food safety culture research. (October 2016) - Nyarugwe, Shingai P.; Linnemann, Anita; Hofstede, Gert Jan; Fogliano, Vincenzo; Luning, Pieternel A.
Abstract: Background: Foodborne outbreaks continue to occur regardless of existing food safety measures indicating the shortcomings of these measures to assure food safety. This has led to the recognition of food safety culture as a key contributory factor to the food safety performance of food establishments. Scope and approach: The aim of this paper is to identify determinants for conducting food safety culture research, using the systems approach as the underlying philosophy to guide the structured reconsideration of national, organisational and safety culture literature, in view of food safety. Key findings and conclusions: Food safety culture is complex and many interlinking factors are at play. The analysis of 'culture' literature showed that food safety culture research should acknowledge the impact of national culture, specify hierarchical level(s) (strategic, tactical, and operational), establish underlying mechanisms, and consider the company's food risks and context characteristics. Major elements to be considered in food safety culture research include organisational and administrative characteristics (i.e. food safety vision, communication, commitment, leadership, training), technical facilities/resources (i.e. food hygiene/safety tools, equipment, & facilities), employee characteristics (i.e. attitudes, knowledge, perceptions and risk awareness), group characteristics, crucial FSMS characteristics, and actual food safety performance. Methodological requirements for food safety culture research include use of the systems approach, measurable indicators, classification systems for differentiated assessment, and use of multiple methods to enhance research validity. The identified food safety culture research determinants provide an underpinned and transparent starting point to the common understanding and research of food safety culture. Highlights: Food safety culture is a key contributor to food safety performance. Systems approach can be used to identify food safety culture research determinants. Determinants derived from national, organisational and safety culture aspects. Identified determinants enable appropriate assessments and interventions.